Locality, Universalism, and Modernity in khutbas for Polish Muslims - Chudziak, Mateusz (Journal of Muslims in Europe, 2026)
The article presents the results of research on sermons delivered in mosques belonging to three Polish Muslim organisations: Muslim Religious Union (MZR), Muslim League (LM), and Sakinah Foundation (FS). The analysis focuses on the strategies adopted by Polish Muslim preachers who, in their sermons (khutbas), try to address issues that are important for the life and identity of the Muslim minority in Poland. Among these issues are: the embedding of Islam in Polish social reality as a fully-fledged part of the Polish cultural context; the relationship of teachings based on the Qur’anic revelation to the challenges of modernity; the links between minoritarian identity and universalism, religion, and science, or the precepts of Islam and the population management practices characteristic of modern societies. The detailed analysis suggests ways of resolving potential dilemmas that may arise for a Muslim from the tensions in these areas.